Influence of different post-endodontic restorations on the fatigue survival and biomechanical behavior of central incisors - De Andrade, Guilherme S. [UNESP]; Tribst, João Paulo M [UNESP]; Orozco, Esteban If [UNESP]; Augusto, Marina G.; Bottino, Marco A. [UNESP]; Borges, Alexandre Ls [UNESP]; Anami, Lilian C.; Saavedra, Guilherme deSFA [UNESP] (My University, 2020)
PURPOSE: To evaluate the influence of different post-endodontic techniques on the fatigue survival and biomechanical behavior of crowned restored central incisors. METHODS: The crowns of 69 bovine incisors were cut, and the roots were treated endodontically and assigned randomly into three groups (n=23): resin composite buildup (BUP), glass fiber post-retained resin composite buildup (GFP), and cast post-and-core (CPC). They received full crown preparation with 2 mm ferrule, and a leucite-reinforced ceramic crown was cemented adhesively. Three specimens from each group were tested monotonically. The remaining specimens were subjected to the stepwise stress fatigue test until fracture or suspension after 1.5 x 10⁶ cycles in a chewing simulator. The load and step at which each specimen failed were analyzed by Kaplan-Meier and Mantel-Cox (log-rank test) statistics, followed by multiple pairwise comparisons, at 5% significance level. The three groups tested (BUP, GFP, and CPC) were 3D modeled (Rhinoceros 4.0) and the maximum principal stress (MPa) criteria were used to calculate the results using FEA. RESULTS: There was no statistical difference between the treatments regarding the load or the number of cycles (Mantel-Cox log-rank test for trend, X²= 0.015, df=1, P= 0.901, X²=3.171, df=1, P= 0.995). Crown cracks were the predominant failure mode, and oblique root fractures were only observed in groups GFP and CPC. In endodontically treated incisors with a 2-mm ferrule, the post-endodontic treatment had no significant effect on fatigue survival. Non-restorable fractures only occurred in teeth restored with posts. CLINICAL SIGNIFICANCE: Although the clinical significance of laboratory studies has some limitations, this study suggests that composite buildups without posts may be an option for restoring endodontically treated incisors with 2 mm ferrule height.